AJARAN GNOSTIK DALAM JEMAAT EFESUS DI SURAT TIMOTIUS DAN TITUS (GNOSTIC TEACHING IN EFESUS CONGREGATIONS IN TIMOTHY AND TITUS LETTERS) - Widjaja, Imron; Simanjuntak, Horbanus Josua; Embong Bulan, Susanti (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2019)
This paper discusses the Gnostic teachings which pose a great danger to the true faith of the Ephesians in the Epistles of Timothy and Titus. This gnostic teaching is categorized as heresy and the instructor is called heresy teacher. It was described as pervasive words, like cancer (2 Tim.2: 17). Paul writes of how dangerous the Gnostic teachings and teachers are. They pretend to know, even though they don't know anything. The disease looks for questions and worries, which causes envy, injury, slander, suspicion and strife among people who are no longer healthy and right minded (1 Tim 6: 4-5). That is why, Paul said: